THE EFFECTIVENESS OF PSYCHOEDUCATIONAL PROGRAMS AT REFUGEE SCHOOLS IN MALAYSIA: A FEASIBILITY STUDY - Abu Yazid Abu Bakar; Ahmed Hamdi Aissa; Salleh Amat (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2025)
This concept paper proposes research to examine the effectiveness of psychoeducational programs provided at refugee schools in Malaysia as counselling intervention. The current provision of such programs is commonly dealing with the pupils’ emotional well-being, behavior, social skills, acculturation, resilience, study skills, and career awareness; however, there is no validation study to examine the correlations between the variables just yet. The proposed research is going to engage the Cognitive Behavioral Theory (CBT) as the main underpinning theory, with the ultimate aim to develop and introduce a psychoeducational module as intervention to help the students’ growth. The module is going to be constructed using mixed method approach, combining both quantitative and qualitative feedback from all involved stakeholders, the pupils, teachers, parents, and school administrators.